Food insecurity is associated with food diversity, depression and blood pressure among rural and urban high school students in Kurdish population: Food insecurity, food diversity and mental health - Arzhang, Pishva; Pourghassem Gargari, Bahram; Bagheri, Amir; Nattagh Eshtivani, Elyas; Ghavami, Abed; Mohammadi, Farzad; Rahmanabadi, Alireza (Progress in Nutrition, 2020)
Introduction: Due to lack of data on the food insecurity and food diversity in the west of Iran, thisstudy conducted to assay food insecurity and its association with food diversity, depression and blood pressureamong Kurdish population focusing on high school students and their families. Method: This cross-sectionalstudy was conducted between September and March, 2015-2016 on 364 high-school students (68.68% urbanand 31.32% rural) and their families. Food security questionnaire, general socio-economic questionnaire(SEQ) and food frequency questionnaire (FFQ). Beck’s Depression Inventory (BDI) test was used to assessdepression condition. Data analysis was performed with SPSS22 and P value less than 0.05 was consideredto be statistically significant. Result: Participants with food diversity less than the median (group2) had moreassociated to food insecurity in all participants (P=0.02). Moreover, in total population dairy diversity wasnegatively associated with food insecurity (p=0.05). No association was observed between food insecurity anddepression among all participants (P=0.54) but after splitting to sex it was significant for female (P=0.02)but not male (P=0.48). Conclusion: food insecurity is associated with different complication in high-schoolstudents in the Kurdish population, west of Iran. Food insecurity which is related to low income is related alsoto low food diversity and other aspects of life such as mental problems, as mentioned depression.